Kinetics of thermally activated triplet fusion as a function of polymer chain packing in boosting the efficiency of organic light emitting diodes. (December 2018) - Dey, Amrita; Chandrasekaran, Naresh; Chakraborty, Dwaipayan; Johari, Priya; McNeill, Christopher; Rao, Akshay; Kabra, Dinesh
Abstract Understanding the photophysical process governing the operation of the organic light emitting diodes (OLEDs) and how they are affected by film morphology is crucial to the efficient design of future OLEDs. In particular, delayed fluorescence (DF), is known to contribute a significant fraction of the light emission from polymer-based OLEDs, but its mechanism remains unclear. Here, we investigate the origin of DF in the state of the art OLED polymer Poly (9, 9-dioctylfluorene-alt-benzothiadiazole) (F8BT), under both optical and electrical excitation using time-resolved emission spectroscopy (TRES) as a function of film thickness, excitation fluence, magnetic-field, and temperature. The temperature dependence of the DF for various film thicknesses suggests that thermally activated triplet migration is the dominant process controlling DF at room temperature. We found that thermal activation energy (E eff ) of triplet migration decreases from 179 ± 31 meV to 86 ± 11 meV as film thickness varied from ~110 nm to ~560 nm, respectively. TheE eff of triplet migration is found to be a function of the molecular packing of polymer chains as determined from synchrotron grazing incidence wide angle x-ray scattering (GIWAXS) studies and steady-state photoluminescence studies. Quantum chemical calculations of reorganization energy and singlet–triplet exchange energy gap in F8BT molecule as a function of the dihedral angle between donor & acceptor moiety also confirm the experimental results. Our results show that DF in polymer OLEDs is significantly affected by parameters such as the film thickness and disorder, allowing for a high degree of control over the underlying photophysics to be achieved. Brighter OLEDs: role of chain packing revealed The detailed time-resolved photophysical studies stress the importance of the morphology of the polymer chains on designing high efficiency organic light emitting diodes. A collaborative team lead by Prof Dinesh Kabra from Indian Institute of Technology Bombay conducts systematic investigations on the decay kinetics and the mechanism of the delayed fluorescence in a typical F8BT based polymeric light-emitting diodes. Through time-resolved emission spectroscopy as a function of film thickness, excitation fluence, magnetic-field, and temperature, they show that the main process controlling the delayed fluorescence is thermally activated triplet-triplet annihilation. They further show that the triplet transport is highly dependent on the molecular packing order and film thickness of the F8BT polymer, opening feasible gateways for molecular engineering of polymer LEDs.